Reply to the 'Comment on "Zemplén transesterification: a name reaction that has misled us for 90 years"' by G. Poli, C. Pezzetta, I. Leito and S. Tshepelevitsh, Green Chemistry, 2018, 20, DOI: 10.1039/c7gc03795c 1. Issue 10 (30th April 2018) - Ren, Bo; Ge, Jiantao; Dong, Hai
Abstract : This article provides our response to a comment on our article that appeared in Green Chemistry . The rate constants of transesterification catalysed by NaOH are larger than those catalysed by MeONa. Abstract : Prof. Poli and co-workers recently commented on our previous report in which we demonstrated that using NaOH and NaOMe in methanol for deacylation are identical. By consideration of the equilibrium between methoxyl and hydroxyl anions, they proposed that the methoxyl anion-catalysed mechanistic path still holds in the deacylation when using NaOH. In theory we believe that their explanation is reasonable. However, our experimental results showed higher transesterification rates when using NaOH than when using MeONa, which may indicate that the hydroxyl anion-catalysed mechanistic path also plays a key role when using NaOH.